TREATMENT OF ENDOGENOUS FUNGAL ENDOPHTHALMITIS - Xhevat Lumi; Mojca Globočnik Petrovič (Zdravniški Vestnik, 2004)
Background. To report clinical findings and treatment possibilities of patients with endogenous fungal endophthalmitis. Methods. Records of patients with endogenous fungal endophthalmitis treated at Eye Clinic from January 2000 to July 2003 were retrospectively reviewed. Information obtained from the medical record include the patient age, sex, causative organism, ocular treatment, systemic antifungal treatment, complications, length of follow-up and final visual outcome. Results. 12 patients (13 eyes)were enrolled (9 males, 3 females, age 18 to 35). Clinical signs of infection cleared and visual acuity improved in all 13 eyes. Conclusions. Pars plana vitrectomy in combination with intravitreal injection of amphotericin B and oral fluconazole is an effective alternative in managament of endogenous fungal endophthalmitis in selected cases.